Animated Video-Based Education on Increasing Mothers' Knowledge about Breastfeeding Techniques in Postpartum Mothers at Bahagia Regional Hospital - Juwita; Asli, Kartika (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2026)
Introduction: Breast milk (ASI) is the best nutrition for the growth and development of infants. However, the coverage of exclusive breastfeeding in Indonesia is still low, including in West Seram Regency. One of the factors that causes low breastfeeding success is the lack of knowledge of mothers about the correct breastfeeding techniques. Education with animated video media is one of the effective methods in improving the understanding of postpartum mothers. Objective: This study aims to determine the effect of animated video-based education on increasing maternal knowledge about breastfeeding techniques in postpartum mothers at Piru Regional Hospital. Research Method: This type of research is quantitative with a one-group pretest-posttest design. The sample in this study were postpartum mothers who met the inclusion criteria. The instrument used was a questionnaire on knowledge of breastfeeding techniques measured before and after the intervention. Data were analyzed using statistical tests using the Wilcoxon test. Results of the study: based on the results of the analysis, there was an increase in knowledge scores after being given education using animated videos about breastfeeding techniques. The results of the statistical test showed a significant value of 0.000 (p <0.05) H0 was rejected Ha was accepted, Conclusion: so it can be concluded that there is an effect of animated video-based education on increasing maternal knowledge about breastfeeding techniques in postpartum mothers in Piru Regional Hospital.